2016
DOI: 10.18632/oncotarget.13216
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 5-FU sensitivity by the proapoptotic rpL3 gene in p53 null colon cancer cells through combined polymer nanoparticles

Abstract: Colon cancer is one of the leading causes of cancer-related death worldwide and the therapy with 5-fluorouracil (5-FU) is mainly limited due to resistance. Recently, we have demonstrated that nucleolar stress upon 5-FU treatment leads to the activation of ribosome-free rpL3 (L3) as proapoptotic factor. In this study, we analyzed L3 expression profile in colon cancer tissues and demonstrated that L3 mRNA amount decreased with malignant progression and the intensity of its expression was inversely related to tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 48 publications
(73 reference statements)
3
48
0
Order By: Relevance
“…On the other hand, ABC family proteins, such as Multi Drug Reactivity 1 (MDR1), are related to multiple drug resistance in cancer. We have previously demonstrated that uL3 is able to negatively control Pgp expression in colon cancer cells by regulation of MDR1 mRNA stability [24]. Moreover, we also demonstrated that the loss of uL3 and the consequent upregulation of the cystathionine β synthase (CBS) enzyme correlated with ineffectiveness of 5-FU in lung and colon cancer cell lines [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, ABC family proteins, such as Multi Drug Reactivity 1 (MDR1), are related to multiple drug resistance in cancer. We have previously demonstrated that uL3 is able to negatively control Pgp expression in colon cancer cells by regulation of MDR1 mRNA stability [24]. Moreover, we also demonstrated that the loss of uL3 and the consequent upregulation of the cystathionine β synthase (CBS) enzyme correlated with ineffectiveness of 5-FU in lung and colon cancer cell lines [23].…”
Section: Resultsmentioning
confidence: 99%
“…We have also previously observed a reduction of uL3 levels in Cisplatin resistant A549 cells [25] that, unlike Calu-6 cells, are proficient for p53, suggesting that the loss of uL3 could be considered a general mechanism of multidrug resistance independent of p53 status. Furthermore, we demonstrated that the loss of uL3 was associated with the up-regulation of the MDR1 mRNA level and Pgp transporter encoded by MDR1 in colon cancer cells [24]. According to this, the multidrug resistance in rCalu-6 cells is associated to the high expression of the human MDR1 gene and the Pgp protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in TP53 null colon cancer cells, 5‐FU (5‐fluorouracil) can cause nucleolar stress to lead to cell cycle arrest and apoptosis. The nucleolar stress induced by 5‐FU can further activate rpL3 (ribosomal protein L3), which induce the expression of its target gene CDKN1A and regulates it's another target gene CBS (cystathionine‐beta‐synthase) to induce mitochondrial apoptosis characterized by an increase of BAX . This suggests that it is worth to explore whether oridonin can lead to cell cycle arrest and apoptosis via p53‐independent pathways, such as inducing nucleolar stress to regulate ribosomal proteins like rpL3.…”
Section: Discussionmentioning
confidence: 99%